The Effect of _Dobbs v. Jackson Women’s Health Organization_ on Clinical Diagnosis of Postpartum Depression - Onur Baser; Yuanqing Lu; Facundo Sepulveda; Ariani Alemzadeh; Amy Endrizal (Journal of Health Economics and Outcomes Research)
# Background The 2022 US Supreme Court decision in _Dobbs v. Jackson Women’s Health Organization_ eliminated the constitutional right to abortion and activated trigger laws in 21 states, either banning or significantly restricting abortion access. This study estimated changes in postpartum depression (PPD) diagnoses after _Dobbs_ in states with trigger laws vs those without.